2004
DOI: 10.1177/088307380401900608
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Hypotonia: Is There an Algorithm?

Abstract: This study was performed with the aim of determining the diagnostic profile of newborns with hypotonia and of analyzing the usefulness of different procedures in the diagnostic process. One hundred thirty-eight hypotonic newborns were identified through the search of hospital records in a 10-year period: 121 (88%) had central hypotonia and 13 (9%) had peripheral hypotonia, whereas 4 (3%) remained unclassified. Analysis of the contribution of clinical data and results of investigations led to the construction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
46
1
6

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 7 publications
5
46
1
6
Order By: Relevance
“…Cerebral causes predominate and one series (12) suggested that this group of disorders might explain up to 88% of cases. Prader-Willi syndrome was particularly important.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cerebral causes predominate and one series (12) suggested that this group of disorders might explain up to 88% of cases. Prader-Willi syndrome was particularly important.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have addressed the relative frequency of the various causes of neonatal/infantile hypotonia (11,12). Cerebral causes predominate and one series (12) suggested that this group of disorders might explain up to 88% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Hipotoni; %60 oranında genetik ve metabolik nedenlerle oluşmaktadır (6,7,10). Çalışma grubumuzun büyük bölümünü genetik sendromlar ve metabolik hastalıklar oluşturmuştur.…”
unclassified
“…The selective use of neuroimaging, genetic studies, and biochemical investigations can contribute to a diagnosis in an additional subset of patients. Invasive studies with EMG and muscle biopsy only contribute to a small fraction of diagnoses 15 (Table 5). …”
Section: Introductionmentioning
confidence: 99%